Combined Application of Chemical and Organic Fertilizers Promoted Soil Carbon Sequestration and Bacterial Community Diversity in Dryland Wheat Fields - Hongmei Song; Zixuan Chang; Xuan Hu; Yan Li; Chengjiao Duan; Lifan Yang; Haoying Wang; Tingliang Li (Land, 2024)
The use of fertilizers is mainly adopted in arid regions to improve the soil carbon (C) pool and crop productivity. However, the mechanisms underlying improvements in dryland wheat field soils related to microbial metabolic activity and community structure remain poorly understood. Therefore, a field experiment with four fertilization treatments and no fertilizer as the control (CK) was conducted for 10 years in a semi-arid region of China. The results revealed that the combined application of chemical and organic fertilizers (fermented chicken manure) clearly increased the levels of soil organic carbon (SOC), dissolved organic carbon (DOC), and light-fraction organic carbon (LFOC) by 13.54–16.72%, 6.96–9.01%, and 11.00–13.51%, respectively, compared to the sole use of chemical fertilizers (FP treatment). Moreover, the combined treatment not only enhanced the metabolic activity of microorganisms concerning carbon source utilization but also increased the diversity of the bacterial community. This caused noticeable changes in the composition of the bacterial community. A Mantel test analysis revealed that Bacteroidetes and Mortierellomycota significantly enhanced the metabolic activity associated with carbohydrate, amino acid, and carboxylic acid C sources. Actinobacteria, Bacteroidetes, and Mortierellomycota facilitated the accumulation of active C and particulate organic carbon (POC), whereas Mortierellomycota specifically promoted the accumulation of heavy-fraction organic carbon (HFOC), thereby collectively influencing the SOC content. The combined application of chemical and organic fertilizers increased the abundance of Bacteroidetes and Mortierellomycota. This enhancement improved the metabolic utilization of carbohydrates, amino acids, and carboxylic acids, resulting in alterations in the types and quantities of soil metabolites. Consequently, these alterations ultimately affect the composition and quantity of the SOC pool in arid agroecosystems. In conclusion, the combined application of balanced NPK fertilizers and organic fertilizers has a strong positive effect in improving soil microbial activity and the soil C pool.